Pink the history of a punk, pretty, powerful colour - Steele, Valerie 1955-; Landis, Deborah Nadoolman 1952-; Albinson, Cassandra ca. 20. Jh; Blaszczyk, Regina Lee ca. 20. Jh; Grisard, Dominique 1971-; Melendez-Escalante, Tanya; Monden, Masafumi ca. 20. Jh (Thames & Hudson, 2018)
"Today, with the advent of 'millennial pink', the colour formerly associated with Barbie has acquired a new identity. Nor is this the first time the symbolism of pink has been radically transformed. In this volume, in collaboration with a major exhibition at the Museum at the Fashion Institute of Technology, New York, curator and fashion historian Valerie Steele explores the history and significance of pink in fashion, art and culture from the 18th century to the present. Steele and her co-authors tell the whole story of this controversial colour, emphasizing how its meanings changed throughout the centuries and across the globe, in cultures as diverse as France, India, Japan, Mexico and the United States. In 18th-century France, men and women alike wore pink, which was a fashionably 'new' colour. A century later, however, pink had become feminized and eroticized in the West (although it took longer for pink-versus-blue gender coding to develop). 'Pink' is beautifully illustrated, with illustrations of stunning pink fashions given context by photographs, advertisements and works of art. It features essays by scholars across the disciplines, giving readers access to a wealth of research into subjects as diverse as Hollywood films and the symbolism of the pink triangle. This book will appeal to all those interested in fashion and culture, as well as those who love pink"--Publisher's description
Includes texts by Valerie Steele, Deborah Nadoolman Landis, A. Cassandra Albinson, Regina Lee Blaszczyk, Dominique Grisard, Tanya Melendez-Escalante and Masafumi Monden ; exhibition curated by Valerie Steele, Director, The Museum at FIT.
Keywords: Geschichte; Geschichte 1700-2018; Bedeutung; Mode; Kultur; Farbe; Rosa; Farbenpsychologie; Verwendung; Kleidung; Color / Psychological aspects / Exhibitions; Color in clothing / Social aspects / Exhibitions; Pink / History / Exhibitions; Pink / Social aspects / Exhibitions; Pink / Psychological aspects / Exhibitions; Fashion / History / Exhibitions; Ausstellungskatalog -- Fashion Institute of Technology -- 07.09.2018-05.01.2019 -- New York, NY